Prevalence and Molecular Characterization of Plasmid-mediated Extended-Spectrum β-Lactamase Genes (bala(TEM), bla(CTX )and blA(SHV)) Among Urinary Escherichia coli Clinical Isolates in Mashhad, Iran - Nakhaei Moghaddam, Mahboobeh (Mashhad University of Medical Sciences, 2012)
OBJECTIVE(S): Extended-spectrum beta-lactamase (ESBL) producing bacteria have an important role in nosocomial infections. Due to the limited availability of information about the molecular epidemiology of ESBL producing bacteria in Mashhad, we decided to investigate about TEM, CTX and SHV ESBLs among urinary Escherichia coli isolates in Mashhad, a city in northeast Iran. MATERIALS AND METHODS: One hundred and eleven clinical isolates of E. coli were diagnosed from hospitalized patients in 2009. After performing antibiogram and phenotypic confirmation test, polymerase chain reaction (PCR) was performed by bla(TEM), bla(SHV) and bla(CTX) primers and restriction digestion was carried out using PstI and TaqI (Fermentas-Lithuania) for confirmation. RESULTS: ESBL producers of E. coli isolates were 33.3%. Among 37 ESBL-producing isolates, 35 (94.6%), 21 (56.8%) and 5 (13.5%) were shown to have bla(CTX), bla(TEM) and bla(SHV), genes respectively. Co-resistance to non-beta lactam antibiotics was observed more with ESBL producers (P < 0.05). CONCLUSION: The results showed that the studied ESBL genes are found with high prevalence and among them bla(CTX) is more widespread in urine E. coli isolates in Mashhad.